On the Surfaces with Constant Mean Curvature along a Curve in the Lie Group - Yuzbasi, Zuhal Kucukarslan; Taze, Sevinç (My University, 2023)
In this study, an isoparametric curve and its Frenet frame are linearly combined to form a surface in 3-dimensional Lie group. When the surface has a constant mean curvature along the given curve, sufficient conditions have been satisfied. In conclusion, we provide examples of our findings and draw graphs.
Keywords: Mean curvature; Lie Group; Surface.